"Just as much as there is Islamophobia, there is racism:" corporeal encounters with the Muslim Other in Amsterdam. Issue 4 (21st April 2023) - Shaker, Reza; van Hoven, Bettina; van Lanen, Sander
ABSTRACT: Conceptualizing Othering as an intercorporeal encounter in urban space, the paper explores how Otherness is lived in the networks of everyday embodied urban living of young Muslims. We provide an in-depth understanding of the ways through which corporeal Othering is spatially organized and practised within everyday urban space felt and lived with different intensities and registered in the sensing bodies of young Muslims as part of their lived embodied urbanism in Amsterdam. We shed light on how the (re)construction of the Muslim Other is spatialized concerning intersectionality, clothing, and stereotyping.